Survey on the effectiveness of university student visits in the context of educational aid to Xinjiang - Li Bo; Dai Quan; Shao Ling (SHS Web of Conferences, 2023)
The survey on the effect of university students' study visits in this study is based on the statistical and survey data of A University, which involves the statistics of study visits from 2015-2019, and 180 students and teachers' questionnaires from 13 visiting universities were completed. The main findings are that the overall evaluation satisfaction of the effect of study visits reached 97%, among which the recognition of professional knowledge and study ability improvement reached about 70%, and the participating students strengthened their awareness of further study and increased The study proposes to promote the study visits of university students in Xinjiang. The study proposes the main suggestions to promote the improvement of the effect of study visits for college students in Xinjiang universities, which are to moderately increase the difficulty of professional courses in Xinjiang universities, to increase the support for study visits by means of special scholarships, and to actively develop the scope of study visits and exchanges, etc.